Acrylate azo amine chain extender, preparation method and application thereof
Patent Information
- Application Number
- CN202311184781.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-14
- Publication Date
- 2026-10-23
- Estimated Expiration
- 2043-09-14
AI Technical Summary
该专利虽然在主链结构中引入不饱和双键结构,但并未对聚氨酯的降解性起到有利作用
[0029]本发明的丙烯酸酯偶氮胺类扩链剂,扩链剂一端为胺基另一端为不饱和双键,由于该特殊结构,将反应进程分为两部分。首先在与异氰酸酯混合后,一端的胺基快速与异氰酸酯进行反应,生成脲键,完成初期扩链反应;但同时其另一端的不饱和双键起到封端作用,暂停了扩链反应的快速进行,避免了二胺扩链剂因活性过高导致体系黏度增长过快,影响整体操作性的问题。这使得在扩链反应第一阶段反应体系活性明显降低,降低体系黏度增长速度,显著提升了流动性与浸润性,有利于制品整体的力学性能。同时由于异氰酸酯键在第一阶段已与胺快速反应完,使该体系在具备较好操作性的同时,降低了对环境湿度的敏感度,提升了使用环境的容忍度。在扩链第二阶段通过外部加热方式,将分子链末端双键打开,使体系中大分子链间完全交联,达到完全熟化效果,获得最终制品。由此可知,使用该类新型扩链剂,反应进程更为可控,在保证前期操作性的同时,可根据需要使其完全熟化,获得最终制品。
Smart Images

Figure CN119613288B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of polyurethane technology, specifically relating to an acrylate azoamine chain extender, its preparation method, and its application. Background Technology
[0002] Chain extenders are commonly used additives in polyurethane formulations. They extend the hard segment molecular chains of polymers, generating linear molecules with larger molecular weights, increasing the hard segment content, and thus improving the overall mechanical properties of the product. Amine chain extenders are an important type. Because they react with isocyanates to form urea bonds, they possess excellent mechanical properties. Furthermore, they exhibit high reactivity with isocyanates. These characteristics combined make them applicable to polyurethane coatings, polyurethane elastomers, and polyurethane adhesives.
[0003] Polyurethane is a cross-linked polymer material obtained by thermosetting isocyanates, polyester polyols, or polyether polyols. Its raw materials are entirely dependent on petroleum-based resources. With societal progress and development, petroleum resources are dwindling, inevitably limiting the development of the polyurethane industry. Furthermore, polyurethane materials are difficult to recycle after disposal and are also difficult to degrade in the natural environment, potentially causing "white pollution." The main methods for treating polyurethane waste are landfill and incineration. Landfill disposal consumes land resources and causes soil degradation, while incineration produces large amounts of toxic gases, easily causing air pollution. Therefore, developing environmentally friendly, biodegradable polyurethane materials has become a focus in the materials science field.
[0004] In recent years, research on biodegradable polyurethane has become a hot topic. Patent CN112979912B provides an ultra-tough polylactic acid-based polyurethane urea material, using polylactic acid diol as the soft segment, and achieving excellent mechanical strength through formulation adjustment. However, the biodegradable portion of this system is only the polyol component, i.e., the soft segment of the polyurethane. A large number of undegradable hard segments remain, thus limiting the overall degradation effect. Patent CN104387553A provides a method for preparing a biodegradable unsaturated polyurethane material, using unsaturated polyester polyol polypropylene fumarate as the soft segment, utilizing the biodegradability of the polyester to achieve the material's biodegradability. Simultaneously, the polyurethane main chain structure contains numerous unsaturated electron-deficient double bonds, facilitating further modification of the material. Although this patent introduces unsaturated double bond structures into the main chain structure, it does not significantly improve the biodegradability of the polyurethane. Summary of the Invention
[0005] The purpose of this invention is to provide an acrylate azoamine chain extender. This chain extender, due to the presence of a terminal amine in its structure, reacts with isocyanates to form urea bonds, effectively improving the tensile strength, hardness, and other mechanical properties of polyurethane products. The unsaturated double bond at the other end controls the extent of the reaction, preventing complete cross-linking of the macromolecular chains in the system, thus maintaining good flowability and wettability over a long period, greatly improving workability. Simultaneously, polyurethane products using this chain extender can be guaranteed to decompose under certain external conditions. Since the chain extender pertains to the hard segment of polyurethane, its own degradation solves the degradation problem of the hard segment. The alkanolamine monomers released during degradation effectively promote the decomposition of polyester polyols in the system due to their alkalinity, thereby achieving effective degradation in both soft and hard segments and improving the overall degradation capability of polyurethane products.
[0006] Another object of the present invention is to provide a method for preparing such acrylate azoamine chain extender.
[0007] Another object of the present invention is to provide the application of this acrylate azoamine chain extender.
[0008] To achieve the above-mentioned objectives, the technical solution of the present invention is as follows:
[0009] An acrylate azoamine having the general structure of formula (I):
[0010]
[0011] Wherein, R1 is a C1-C5 alkyl group, such as an alkyl group with 1, 2, 3, 4, or 5 carbon atoms. The alkyl group can be a straight-chain alkyl group or a branched alkyl group, preferably a C1-C4 alkyl group; specifically, for example, CH2, CH2CH2, CH2CH2CH2, CH2CH2CH2CH2, CH2CH2CH2CH2, etc., preferably any one of CH2, CH2CH2, and CH2CH2CH2; R2 is a group containing an aromatic ring or an alicyclic ring, that is, a group structure with at least one benzene ring or alicyclic ring, such as diphenylmethane, dicyclohexylmethane, benzene, alkylbenzene, etc.
[0012] In one specific embodiment, the structure of the acrylate azoamine chain extender is as follows:
[0013]
[0014] On the other hand, a method for preparing the aforementioned acrylate azoamine chain extender includes the step of reacting an aminoalkyl acrylate with an aromatic diamine or an alicyclic diamine monomer in the presence of a metal catalyst to generate an acrylate azoamine.
[0015] The alkyl acrylate has the general formula (II):
[0016]
[0017] In equation (II), the selection of R1 is the same as in equation (I) above.
[0018] The aromatic diamine monomer or alicyclic diamine monomer has the structural formula NH2-R2-NH2, where R2 is a group containing an aromatic ring or alicyclic ring, and the selection of R2 is consistent with that in the aforementioned formula (I).
[0019] The reaction equation is:
[0020]
[0021] The molar ratio of the aminoalkyl acrylate to the aromatic diamine or alicyclic diamine monomer is 1:1 to 5, for example, 1:1, 1:1.5, 1:2, 1:2.5, 1:3, 1:4, 1:4.5, 1:5, etc., preferably 1:1 to 3.
[0022] The metal catalyst is selected from any one of zinc, bismuth, and tin, and is usually an elemental metal, preferably zinc, such as zinc powder.
[0023] The amount of the metal catalyst added is 1 to 5% of the sum of the molar amounts of the aminoalkyl acrylate and the aromatic diamine and alicyclic diamine monomers, for example, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, etc., preferably 2 to 3%.
[0024] The reaction temperature for the above-mentioned aminoalkyl acrylates with aromatic diamines and alicyclic monomers is 60-120℃, such as 60℃, 70℃, 80℃, 90℃, 100℃, 110℃, 120℃, etc., and the reaction time is 2-5h, such as 2h, 2.5h, 3h, 4h, 5h, etc.
[0025] In one specific embodiment, the preparation method of the acrylate azoamine chain extender includes: adding alkyl acrylate, aromatic diamine / alicyclic diamine and zinc powder catalyst into a reactor, and reacting at 60-120°C for 2-5 hours to generate acrylate azoamine.
[0026] On the other hand, the aforementioned acrylate azoamine chain extenders or acrylate azoamine chain extenders prepared by the aforementioned methods are used in the preparation of polyurethane.
[0027] The acrylate azoamine chain extender of the present invention can be used alone or in combination with other chain extenders. For example, it can be mixed with polyether and plasticizer as a curing agent component for the production of polyurethane-related products. These products can be applied to composite materials, elastomers and other fields.
[0028] Compared with the prior art, the beneficial effects of the present invention are as follows:
[0029] The acrylate azoamine chain extender of this invention has an amine group at one end and an unsaturated double bond at the other. Due to this unique structure, the reaction process is divided into two parts. First, after mixing with isocyanate, the amine group at one end reacts rapidly with the isocyanate to form a urea bond, completing the initial chain extension reaction. Simultaneously, the unsaturated double bond at the other end acts as a capping agent, halting the rapid chain extension reaction and preventing the problem of excessively high viscosity increase due to the high activity of the diamine chain extender, which would affect overall operability. This significantly reduces the activity of the reaction system in the first stage of the chain extension reaction, slows down the viscosity increase rate, and significantly improves flowability and wettability, which is beneficial to the overall mechanical properties of the product. Furthermore, since the isocyanate bond has already reacted rapidly with the amine in the first stage, the system maintains good operability while reducing sensitivity to environmental humidity, thus improving tolerance to the operating environment. In the second stage of chain extension, external heating is used to open the double bonds at the ends of the molecular chains, allowing for complete cross-linking between the macromolecular chains in the system, achieving complete curing and obtaining the final product. Therefore, it can be seen that by using this type of new chain extender, the reaction process is more controllable. While ensuring the operability in the early stage, it can be fully matured as needed to obtain the final product.
[0030] The azo amine and ester bond structure in the acrylate azo amine chain extender of the present invention can be decomposed under certain external conditions (e.g., under alkaline conditions and an ambient temperature of 50°C to 70°C, the azo bond breaks to generate two primary amine structures, and the ester bond hydrolyzes under alkaline conditions to generate carboxylate and alcohol). That is, while the hard segment is decomposed by the chain extender, the presence of the alkaline amine monomer makes the system alkaline. Under alkaline conditions, the decomposition of polyester segments such as polylactic acid and polycaprolactone can be effectively promoted. While achieving the decomposition of hard segments, it also effectively promotes the degradation of soft segments containing polyester segments, thereby enhancing the overall degradation ability of polyurethane products. Detailed Implementation
[0031] The following embodiments will further illustrate the method provided by the present invention, but the present invention is not limited to the listed embodiments, and should also include any other known modifications within the scope of the claims of the present invention.
[0032] Sources of some raw materials:
[0033] MDA-100, IPDA, and HMDA are from Wanhua Chemical Group Co., Ltd.
[0034] ethyl aminoacrylate, butyl aminoacrylate, and hexyl aminoacrylate were purchased from Nanjing Qishi Biotechnology Co., Ltd.
[0035] MDI prepolymer: 200g of C2020 polyether and 400g of F3135 polyether were dehydrated at 110℃ for 2 hours, then cooled to 85℃ and 200g of MDI50 were added to carry out a polymerization reaction to generate MDI prepolymer. Both the polyether and MDI50 were sourced from Wanhua Chemical Group Co., Ltd.
[0036] Example 1
[0037] (1) 2 mol of aminoethyl acrylate and 4 mol of HMDA were added to a dry reactor, and 0.24 mol of zinc powder catalyst was added. The reaction was carried out at 90°C for 2.5 hours. After distillation, azo acrylate was obtained.
[0038] (2) Mix 3g of the chain extender obtained in step (1) with 30g of C2020 polyether and 35g of long-chain chlorinated paraffin. After removing water at 105°C for 2.5 hours, mix with MDI prepolymer at a mass ratio of 2:1 and then mix evenly using a stirrer.
[0039] According to the national standard GB / T19250-2013, 2.5 mm thick standard mechanical property test specimens were cast at room temperature. After 2 hours, the mixture could still flow freely within the mold. Post-curing was carried out at 150 degrees Celsius for 8 hours. After curing at room temperature for 7 days, mechanical property tests were conducted. Using a universal tensile testing machine, tests were performed within the tensile speed range required by the national standard. The tensile shear strength of the specimens reached 3.4 MPa, and the elongation at break reached 620%.
[0040] Degradation test: Small sample pieces (10mm × 10mm × 5mm) were cut from the sample plate and immersed in 25ml of phosphate buffer solution (pH = 7.2). The samples were placed at 37±1℃ and removed every 6–7 days. After vacuum drying at 80℃ until constant weight, the samples were weighed and the percentage of mass loss was calculated. After 20 days of immersion, the weight loss rate reached 12.5%.
[0041] Example 2
[0042] (1) Add 2 mol of aminobutyl acrylate and 2 mol of MDA100 to a dry reactor, add 0.04 mol of zinc powder catalyst, react at 120℃ for 2 hours, and then distill to obtain azo acrylate.
[0043] (2) Mix 2g of the chain extender obtained in step (1) with 20g of C2020 polyether and 23g of long-chain chlorinated paraffin. After removing water at 100°C for 2 hours, mix with MDI prepolymer at a mass ratio of 2:1 and then mix evenly using a stirrer.
[0044] According to the national standard GB / T19250-2013, 2.5 mm thick standard mechanical property test specimens were cast at room temperature. After 2 hours, the mixture could still flow freely within the mold. Post-curing was carried out at 150 degrees Celsius for 8 hours. After curing at room temperature for 7 days, mechanical property tests were conducted. Using a universal tensile testing machine, tests were performed within the tensile speed range required by the national standard. The tensile shear strength of the specimens reached 3.8 MPa, and the elongation at break reached 600%.
[0045] Degradation test: Small sample pieces (10mm × 10mm × 5mm) were cut from the sample plate and immersed in 25ml of phosphate buffer solution (pH = 7.2). The samples were placed at 37±1℃ and removed every 6–7 days. After vacuum drying at 80℃ until constant weight, the samples were weighed and the percentage of mass loss was calculated. After 20 days of immersion, the weight loss rate reached 13.6%.
[0046] Example 3
[0047] (1) 2 mol of aminoethyl acrylate and 6 mol of IPDA were added to a dry reactor, and 0.4 mol of bismuth catalyst was added. The reaction was carried out at 120°C for 5 hours. After distillation, azo acrylate was obtained.
[0048] (2) Mix 4g of the chain extender obtained in step (1) with 25g of F3135 polyether and 28g of long-chain chlorinated paraffin. After removing water at 100°C for 2 hours, mix it with MDI prepolymer at a mass ratio of 2.5:1 and then mix it evenly with a stirrer.
[0049] According to the national standard GB / T19250-2013, 2.5 mm thick standard mechanical property test specimens were cast at room temperature. Two hours later, the mixture could still flow freely within the mold. Post-curing was then carried out at 150 degrees Celsius for 8 hours. After curing at room temperature for 7 days, mechanical property tests were conducted. Using a universal tensile testing machine, tests were performed within the tensile speed range required by the national standard. The tensile shear strength of the specimens reached 3.2 MPa, and the elongation at break reached 564%.
[0050] Degradation test: Small sample pieces (10mm × 10mm × 5mm) were cut from the sample plate and immersed in 25ml of phosphate buffer solution (pH = 7.2). The samples were placed at 37±1℃ and removed every 6–7 days. After vacuum drying at 80℃ until constant weight, the samples were weighed and the percentage of mass loss was calculated. After 20 days of immersion, the weight loss rate reached 12.9%.
[0051] Example 4
[0052] (1) 2 mol of aminohexyl acrylate and 10 mol of IPDA were added to a dry reactor, and 0.24 mol of tin catalyst was added. The reaction was carried out at 60°C for 5 hours. After distillation, azo acrylate was obtained.
[0053] (2) Mix 8g of the chain extender obtained in step (1) with 40g of F3135 polyether and 58g of long-chain chlorinated paraffin. After removing water at 100°C for 2 hours, mix with MDI prepolymer at a mass ratio of 3:1 and then mix evenly using a stirrer.
[0054] According to the national standard GB / T19250-2013, 2.5 mm thick standard mechanical property test specimens were cast at room temperature. Two hours later, the mixture could still flow freely within the mold. Post-curing was then carried out at 150 degrees Celsius for 8 hours. After curing at room temperature for 7 days, mechanical property tests were conducted. Using a universal tensile testing machine, tests were performed within the tensile speed range required by the national standard. The tensile shear strength of the specimens reached 3.6 MPa, and the elongation at break reached 552%.
[0055] Degradation test: Small sample pieces (10mm × 10mm × 5mm) were cut from the sample plate and immersed in 25ml of phosphate buffer solution (pH = 7.2). The samples were placed at 37±1℃ and removed every 6–7 days. After vacuum drying at 80℃ until constant weight, the samples were weighed and the percentage of mass loss was calculated. After 20 days of immersion, the weight loss rate reached 11.2%.
[0056] Example 5
[0057] (1) 3 mol of aminopropyl acrylate and 12 mol of HMDA were added to a dry reactor, and 0.45 mol of bismuth catalyst was added. The reaction was carried out at 100℃ for 2.3 hours. After distillation, azo acrylate was obtained.
[0058] (2) Mix 3g of the chain extender obtained in step (1) with 35g of F3135 polyether and 48g of long-chain chlorinated paraffin. After removing water at 100°C for 2 hours, mix with MDI prepolymer at a mass ratio of 2.5:1 and then mix evenly using a stirrer.
[0059] According to the national standard GB / T19250-2013, 2.5 mm thick standard mechanical property test specimens were cast at room temperature. Two hours later, the mixture could still flow freely within the mold. Post-curing was then carried out at 150 degrees Celsius for 8 hours. After curing at room temperature for 7 days, mechanical property tests were conducted. Using a universal tensile testing machine, tests were performed within the tensile speed range required by the national standard. The tensile shear strength of the specimens reached 3.3 MPa, and the elongation at break reached 570%.
[0060] Degradation test: Small sample pieces (10mm × 10mm × 5mm) were cut from the sample plate and immersed in 25ml of phosphate buffer solution (pH = 7.2). The samples were placed at 37±1℃ and removed every 6–7 days. After vacuum drying at 80℃ until constant weight, the samples were weighed and the percentage of mass loss was calculated. After 20 days of immersion, the weight loss rate reached 12.0%.
[0061] Comparative Example
[0062] 2g of 3,3'-dichloro-4,4'-diaminodiphenylmethane (MOCA) was mixed with 20g of C2020 polyether and 23g of long-chain chlorinated paraffin. After dehydration at 100℃ for 2 hours, it was mixed with MDI prepolymer at a mass ratio of 2:1 and then thoroughly mixed using a stirrer. Following the national standard GBT19250-2013, 2.5mm thick standard mechanical property test specimens were cast at room temperature. After 40 minutes, the mixture could no longer flow freely in the mold. Post-curing was carried out at 150℃ for 8 hours. After curing at room temperature for 7 days, mechanical property tests were performed. Using a universal tensile testing machine, the tensile shear strength of the specimen reached 3.0 MPa, and the elongation at break reached 520%.
[0063] For degradation testing, small sample pieces (10mm × 10mm × 5mm) were cut from the sample plate and immersed in 25ml of phosphate buffer solution (pH = 7.2). The samples were placed at 37±1℃ and removed every 6–7 days. After vacuum drying at 80℃ until constant weight, the samples were weighed and the percentage of mass loss was calculated. After 20 days of immersion, the weight loss rate was 1.5%.
Claims
1. An acrylate azoamine chain extender, characterized in that, Having the general formula structure of equation (I): Wherein, R1 is selected from any one of CH2, CH2CH2, CH2CH2CH2, and CH2CH2CH2CH2CH2, and R2 is selected from any one of diphenylmethane residue and dicyclohexylmethane residue; The acrylate azoamine chain extender is generated by reacting an aminoalkyl acrylate with an aromatic diamine or an alicyclic diamine monomer in the presence of a metal catalyst. The structural formula of the aromatic diamine monomer or alicyclic diamine monomer is as follows: , Any one of them.
2. An acrylate azoamine chain extender, characterized in that, It has the following structure: 。 3. An acrylate azoamine chain extender, characterized in that, It has the following structure: 。 4. A method for preparing the acrylate azoamine chain extender according to claim 1, characterized in that, The method includes the step of reacting an aminoalkyl acrylate with an aromatic diamine or an alicyclic diamine monomer in the presence of a metal catalyst to generate an acrylate azoamine.
5. The preparation method according to claim 4, characterized in that, The aminoalkyl acrylate has the general formula (II): R1 is selected from any one of CH2, CH2CH2, CH2CH2CH2, and CH2CH2CH2CH2CH2.
6. The preparation method according to claim 4, characterized in that, The structural formula of the aromatic diamine monomer or alicyclic diamine monomer is as follows: , Any one of them.
7. The preparation method according to any one of claims 4 to 6, characterized in that, The molar ratio of aminoalkyl acrylate to aromatic diamine or alicyclic diamine monomer is 1:1 to 5.
8. The preparation method according to claim 7, characterized in that, The molar ratio of aminoalkyl acrylate to aromatic diamine or alicyclic diamine monomer is 1:1~3.
9. The preparation method according to claim 4, characterized in that, The metal catalyst is selected from any one of zinc, bismuth, and tin.
10. The preparation method according to claim 9, characterized in that, The metal catalyst is zinc.
11. The preparation method according to claim 9, characterized in that, The amount of the metal catalyst added is 1 to 5% of the sum of the molar amounts of the aminoalkyl acrylate and the aromatic diamine and alicyclic diamine monomers.
12. The preparation method according to claim 11, characterized in that, The amount of the metal catalyst added is 2 to 3% of the sum of the molar amounts of the aminoalkyl acrylate and the aromatic diamine and alicyclic diamine monomers.
13. The preparation method according to any one of claims 4 to 6, characterized in that, The reaction temperature is 60~120℃, and the reaction time is 2~5h.
14. The use of the acrylate azoamine chain extender according to any one of claims 1 to 3 or the acrylate azoamine chain extender prepared by the preparation method according to any one of claims 4 to 13 in the preparation of polyurethane.
15. The application according to claim 14, characterized in that, The acrylate azoamine chain extender is used in conjunction with isocyanate and biodegradable polyester polyol.
Citation Information
Patent Citations
Biodegradable unsaturated polyurethane material and preparation method thereof
CN104387553A
Super-tough polylactic acid-based polyurethane urea and its preparation method
CN112979912B
Acrylonitrile modified azo diamine chain extender and preparation method thereof
CN116178205A